Revisiting Eigenberg's prison rape model with criminal justice majors. Issue 3 (2nd September 2021) - Kim, Bitna; Bak, Hyeonna; Garcia, Joshua
ABSTRACT: Prison rape can result in profound physical and psychological damage to inmates. Despite the 2003 Prison Rape Elimination Act, prison rape incidents in the US have increased over 15 years. Previous research results have demonstrated that correctional officers who endorsed rape myths failed to enforce regulations, and they were apt to engage in sexual misconduct or sexual harassment directed toward inmates. It has been almost two decades since Eigenberg ([2000a]. Correctional officers' definitions of rape in male prisons. Journal of Criminal Justice, 28, 435–449) presented the mechanism explaining prison rape myths (PRM) among correctional officers. The present study revisits Eigenberg's (2000a) prison rape model using the survey data from 446 criminal justice (CJ) majors, 119 of whom expressed their interest in corrections as a desired career. For the most part, the findings in this study confirm that Eigenberg's (2000a) model is applicable to the PRM of CJ majors. However, no education effect in relation to PRM was found. Implications for recruitment, training, and education, as well as avenues for future research, are then discussed.